ANALISIS ELEMEN VISUAL POSTER “KONSER URUP” 2024 KUNTO AJI DAN KORELASINYA SEBAGAI MEDIA PROMOSI - Maylano, Arkhan Nauval; Fadhil, Ismu Rasul Muhammad; Zackie Ferdiansyah Yusuf (AKSA: Jurnal Desain Komunikasi Visual, 2025)
This study analyzes the visual elements of the "Konser Urup" 2024 poster featuring Kunto Aji and examines its effectiveness as a promotional medium. The research aims to identify key visual components that attract audience attention and influence their decision to attend the concert. The study employs a qualitative approach, utilizing content analysis to dissect the poster's design elements, including color, typography, imagery, and layout. Findings indicate that the use of vibrant colors, bold typography, and high-quality images of the artist significantly enhance the poster's appeal. Additionally, the strategic placement of information such as date, venue, and ticket details ensures clarity and accessibility for the audience. The study also explores the correlation between these visual elements and audience engagement on social media platforms. Results reveal a positive correlation, with visually appealing posters receiving higher engagement rates, including likes, shares, and comments. This underscores the importance of thoughtful visual design in promotional materials to maximize audience reach and event attendance. The research concludes that incorporating effective visual elements in concert posters is crucial for successful event promotion, offering valuable insights for marketers and designers in the entertainment industry.